Sosialisasi Tanjak Melayu sebagai Potensi Ekonomi Kreatif di SMA Negeri 1 Tanah Putih - Hendra Eka Saputra; Zulkifli Zulkifli; Putri Nuraini (Lok Seva: Journal of Contemporary Community Service, 2023)
The interest and consistency of Malay culture cannot be separated from Islam, this can be seen from the various elements of society who are of Malay blood and even those who are not of Malay blood, always maintaining the preservation of the culture and heritage of the former people. This makes Malay culture an obligation for people who live on Malay land to preserve their ancestral heritage. During this trend, there is a lot of enthusiasm from the community to be able to take part in maintaining this culture. One of them is by producing Malay tanjak and selling it to the public, aiming to make it easier to get Malay tanjak from local business actors. Sustainability later to carry out the practice of making Malay tanjak after the understanding given during the socialization regarding the creative economy and local wisdom based on Malay culture identical to Islam (Malay tanjak) is an excellent potential for those who want to become entrepreneurs in the production of Malay tanjak. Community service targets Tanah Putih 1 Public High School students as an audience and the target of generations who will become successors to preserve Malay culture by buying, producing, and selling it. The hope in this first stage is an understanding of the importance of maintaining cultural preservation and the economic potential of Malay tanjak production in achieving a pioneering business. If the experience has been put together, you can practice making Malay tanjak in activities in the future.